Performance analysis of polarisation shift keying modulation format for optical networks - Lee, L.H.; Geok, T.K.; Reza, A.W. (2010)
Recent studies show that the polarisation shift keying (PoISK) is regarded as one of the most promising modulation formats for future optical networks. Therefore, a novel architecture of PoISK modulation format is presented in this study. This paper also includes performance comparison of PoISK with the conventional Duobinary and non-return-to-zero on-off keying (NRZ-OOK) modulation formats. The obtained results show that the proposed PoISK modulation format can bring significant improvement of about 40% and 52%, respectively than the results obtained by using the conventional Duobinary and the existing NRZ-OOK modulation format.